Between first and second order : a comparison of voting behaviour in European an dlocal elections in Britain - Heath, Anthony (European journal of political research : official journal of the European Consortium for Political Research, 1999)
Abstract (s. 389).
Keywords: kunnallisvaalit : Iso-Britannia; Euroopan parlamentti : vaalit : Iso-Britannia; äänestyskäyttäytyminen